The impact of foreign macroeconomic news on financial markets in the Czech Republic, Hungary, and Poland - David Büttner; Bernd Hayo; Matthias Neuenkirch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
In this paper, we study the effects of euro area and US macroeconomic news on financial markets in the Czech Republic, Hungary, and Poland (CEEC-3) from 1999 to 2006. Using a GARCH model, we examine the impact on daily returns of three-month interest rates, stock market indices, exchange rates versus the euro, and the US dollar. First, foreign macroeconomic news has a significant impact on CEEC-3 financial markets. Second, neither US nor European news has a stronger effect over the whole observation period. Third, the process of European integration is accompanied by an increasing importance of euro area news relative to US news. Fourth, there are country-specific differences: the Czech markets become more affected by foreign news after the Copenhagen Summit than the other countries. Finally, testing the persistence of news over a business week confirms our main results.
Keywords: G12; G15; F30; 330; Financial Markets; Czech Republic; Hungary; Poland; Macroeconomic News; European Monetary Union